Studi Kehilangan Air pada District Metered Area Plamongan Indah di Wilayah Pelayanan Semarang Timur Perumda Air Minum Tirta Moedal Kota Semarang - Patria, Ardhian Elia; Masduqi, Ali; Prinandes, Dades (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Non-Revenue Water (NRW) remains a significant challenge in drinking water supply systems as it affects both technical performance and financial efficiency. In 2024, Perumda Air Minum Tirta Moedal Semarang recorded an NRW level of 44.59%. This study aims to evaluate water losses in the Plamongan Indah District Metered Area (DMA) and to formulate appropriate control strategies. Primary data were obtained through field measurements of flow and pressure and customer meter accuracy tests, while secondary data included network maps, distribution volumes, and consumption records. The analysis was conducted by preparing a water balance using WB-EasyCalc and evaluating leakage performance through the Infrastructure Leakage Index (ILI). The results show that water losses in the Plamongan Indah DMA amounted to 47.53%, or 275,850 m³ per year. These losses consist of 43.19% physical losses (250,693 m³) and 4.33% apparent losses (25,157 m³), with an estimated annual financial impact of IDR 1.603.791.900. The ILI value of 16.04 places the DMA in category D according to the International Water Association classification, indicating a very high leakage rate and inefficient resource utilization. Recommended strategies include implementing active leakage control, applying effective pressure management, replacing customer meters older than five years, and reducing illegal connections. These measures are expected to reduce NRW levels significantly and improve the efficiency of water supply management at Perumda Air Minum Tirta Moedal.